A nitrogen-doped bismuth / carbon composite microsphere material and its preparation method and application

The nitrogen-doped bismuth/carbon composite microsphere material addresses the volume expansion issue in sodium-ion batteries by embedding nano-bismuth in a carbon matrix, enhancing stability and conductivity, thus achieving high capacity and long cycle life.

CN115986090BActive Publication Date: 2025-01-03XIAMEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310065316.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-13
Publication Date
2025-01-03
Estimated Expiration
2043-01-13

Smart Images

  • Figure CN115986090B_ABST
    Figure CN115986090B_ABST
Patent Text Reader

Abstract

The present invention discloses a nitrogen-doped bismuth / carbon composite microsphere material and a preparation method and application thereof, including: a micron carbon sphere matrix material, wherein a plurality of nano-bismuth particles are uniformly embedded inside the micron carbon sphere, each nano-bismuth particle is tightly wrapped by a carbon matrix to form a dense bismuth / carbon composite sphere, and a nitrogen-doped structure; due to the dense spherical structure of the nitrogen-doped bismuth / carbon composite microsphere material, the tight combination of bismuth and carbon, and the doping of nitrogen, when applied to sodium ion batteries, it can effectively alleviate the volume expansion of the material, accelerate the carrier transfer rate, and shorten the charge and discharge time. The present invention provides a method for preparing a nitrogen-doped bismuth / carbon composite microsphere material, including the steps of: S10: preparing bismuth / organic microspheres; S20: the bismuth / organic microspheres in S10 are sintered and carbonized to obtain the nitrogen-doped bismuth / carbon composite microsphere material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery electrode materials, and in particular relates to a nitrogen-doped bismuth / carbon composite microsphere material and a preparation method and application thereof Background Art

[0002] Lithium-ion batteries are widely used in portable electronic products, electric vehicles, large-scale energy storage and other fields due to their high energy density. However, the limited lithium resources in the earth's crust and the low content make the production cost of lithium-ion batteries high and difficult to sustain. Therefore, it is particularly important to develop new energy storage technologies.

[0003] Sodium-ion batteries have shown broad application prospects in the fields of medium- and low-speed electric vehicles, household side, and large-scale energy storage due to their abundant sodium resources (sodium / lithium reserve ratio: >>1000), low cost, and high cost-effectiveness. However, due to the large ionic radius of sodium, traditional commercial graphite and silicon-carbon negative electrodes cannot stably embed sodium. Based on this, the development of suitable sodium-ion battery electrode materials is the key to the development of sodium-ion battery technology.

[0004] Bismuth metal is a metal material with stable physical and chemical properties, large reserves, low price and environmental friendliness. When used as anode material for sodium ion batteries, it has a high theoretical mass capacity (385 mAh / g) and theoretical volume capacity (3773 mAh / cm 3 ), is one of the hot materials currently studied in sodium-ion battery systems. However, when metallic bismuth is used as the negative electrode material of sodium-ion batteries, there is a huge volume expansion (~352%) during the process of sodium insertion and extraction. The huge volume expansion causes the material structure to be damaged, the materials lose connection with each other, resulting in increased interface impedance and material detachment from the current collector, which causes the battery performance to decline or even fail. Most of the existing solutions are to simply coat the surface of bismuth or mix it with carbon materials to form a composite. These methods alleviate the volume expansion of bismuth and improve the cycle stability to a certain extent, but they still cannot solve the problem of capacity decay of bismuth during long-term cycles, especially the problem of too fast capacity decay at higher current density, which limits its commercial application.

[0005] Patent CN 113130873A discloses a method for synthesizing porous bismuth-carbon composite material composite microspheres by direct magnesium heat with bismuth carbonate, the method comprising the following steps: directly mixing bismuth carbonate and magnesium powder, placing them in a stainless steel reactor, reacting them at 500°C under an inert atmosphere to obtain a precursor, and then stirring and pickling them in a tartaric acid solution until no obvious bubbles are generated to obtain the final porous bismuth-carbon product. The invention has a wide range of materials, a simple method, and is green and pollution-free, which provides the possibility for large-scale production; the bismuth-carbon composite material composite microsphere material prepared by this method has a porous skeleton structure, which can alleviate its volume expansion during the charge and discharge process of the sodium ion battery, and the addition of carbon elements during the preparation process greatly improves the conductivity of the material; in the subsequent sodium ion battery test, it shows a high capacity and excellent rate performance and ultra-long cycle stability. Patent CN 114122407A A preparation method and application of a double carbon layer protected bismuth nanoparticle composite material, the preparation method comprising: S1, dispersing a bismuth source and an organic ligand in an organic solvent to obtain a uniform solution; S2, taking the uniform solution for hydrothermal reaction to generate a Bi MOF precursor; S3, dispersing the Bi MOF precursor obtained in step S3 in a Tris buffer solution, adding dopamine hydrochloride under vigorous stirring, and continuing to stir to obtain Bi MOF@PDA; S4, placing the Bi MOF@PDA obtained in step S4 and a nitrogen-containing pore-forming agent in two quartz boats for carbon thermal reduction treatment to obtain a double carbon layer protected bismuth nanoparticle composite material. The overall synthesis method of the present invention is simple, the utilization rate of active substances is high, the electrode material structure is stable, and there are many active sites, which better improves the rate and cycle stability of sodium ion batteries. The above existing technologies are achieved by designing a porous skeleton structure or using double-layer carbon to wrap bismuth particles. Although they can improve the capacity, rate performance and cycle stability to a certain extent, they still cannot meet the current high storage requirements and high-potential cycle stability requirements. They also have high production costs, complex preparation processes, long cycles, low yields, and the generation of other by-products.

[0006] Therefore, it is necessary to alleviate the volume expansion of bismuth during the sodium insertion and deinsertion process through reasonable structural design, stabilize the electrode structure, and fully utilize the high theoretical capacity of metallic bismuth, so as to obtain metallic bismuth negative electrode materials with high specific capacity, long cycle stability and excellent rate performance, thereby promoting its commercial application. Summary of the invention

[0007] In order to solve at least one of the above technical problems, the present invention proposes a nitrogen-doped bismuth / carbon composite microsphere material and a preparation method and application thereof, which can effectively alleviate the volume expansion of bismuth and fully utilize its high theoretical capacity.

[0008] The first aspect of the present invention provides a nitrogen-doped bismuth / carbon composite microsphere material, comprising:

[0009] Micron carbon sphere matrix material, wherein a plurality of nano-bismuth particles are uniformly embedded inside the micron carbon sphere, and each nano-bismuth particle is tightly wrapped by the carbon matrix to form a dense bismuth / carbon composite sphere, and a nitrogen-doped structure. Nitrogen doping can provide more active sites and provide higher capacity, and can effectively improve the conductivity of the carbon material matrix to make carrier transmission faster. Bismuth particles wrapped in carbon matrix have higher stability, and the presence of carbon layer can inhibit the volume expansion of bismuth particles during charging and discharging to a certain extent. The dense structure makes full use of the advantage of bismuth's high theoretical volume capacity, and can provide higher sodium storage capacity in the limited space of the battery system, and has a very broad application prospect.

[0010] Preferably, the carbon in the micron carbon spheres is amorphous carbon.

[0011] Preferably, the average diameter of the micron carbon spheres is 3 μm to 9 μm.

[0012] Preferably, the bismuth nanoparticles have an average diameter of 5 nm to 13 nm, are uniformly embedded in the micron carbon spheres, and have a mass fraction of bismuth of 76% to 90%.

[0013] Since bismuth has a large volume expansion (about 352%) during the cycle when used as the negative electrode material of sodium ion batteries, the particle size of nano-bismuth directly affects the mass fraction of bismuth after the material is composited with carbon. When bismuth-carbon composite microspheres are used as sodium ion batteries, bismuth mainly provides sodium storage capacity. A decrease in the mass fraction of bismuth will lead to a decrease in battery capacity. Excessive bismuth content will increase the overall expansion rate of the material, causing the material to break during the cycle, resulting in battery failure. Therefore, 76%-90% is a more reasonable bismuth content range. The diameter range of carbon spheres is affected by bismuth particles and bismuth content. When bismuth particles and content are limited and composited with carbon, the size range that can be formed is 3μm-9μm due to the carbon density. If the carbon matrix is ​​small, the bismuth content increases, and the above-mentioned adverse effects of excessive bismuth content appear. If the carbon matrix is ​​too large, the bismuth content decreases and the above-mentioned problem of low bismuth content appears.

[0014] Preferably, the type of nitrogen in the nitrogen-doped structure is graphitic nitrogen (graphitic-N), pyridinic nitrogen (pyridinic-N), or pyrrolic nitrogen (pyrrolic-N).

[0015] Preferably, the specific surface area of ​​the nitrogen-doped bismuth / carbon composite microsphere material is 70 m 2 / g~90m 2 / g.

[0016] Reasonable micro-nano structure improves space utilization. That is, nano-bismuth and carbon are combined to form dense micron balls, and both the internal and external spaces of the material are well utilized.

[0017] A more effective bismuth-carbon composite method. The nano-sizing of bismuth can reduce the adverse effects of volume expansion, and the presence of the carbon matrix further limits the volume expansion, resulting in better mechanical properties of the material and a more stable structure during the cycle.

[0018] Moderate specific surface area. Reduce side reactions and electrolyte loss during battery cycling. Under the condition of a certain volume, if the structure is loose, the specific surface area will be relatively large, but too large a specific surface area will consume more electrolyte and produce side reactions when the material is used as a sodium ion battery material, which will have an adverse effect on battery performance. On the contrary, if the structure is denser and the specific surface area is smaller, it will be unfavorable for the electrolyte to contact and infiltrate the material, hinder the occurrence of electrochemical reactions, and also have an adverse effect on the material.

[0019] In a second aspect, a method for preparing a nitrogen-doped bismuth / carbon composite microsphere material is provided, comprising the following steps:

[0020] S10: Preparation of bismuth / organic microspheres;

[0021] S20: The bismuth / organic microspheres in S10 are sintered and carbonized to obtain nitrogen-doped bismuth / carbon composite microsphere materials.

[0022] Preferably, the S10 includes:

[0023] S11: dissolving bismuth nitrate pentahydrate, polyvinyl pyrrolidone, sodium bromide, and glucose in ethylene glycol and 10% nitric acid solution to obtain a mixed solution;

[0024] S12: continuously stirring the mixed solution under magnetic stirring at room temperature;

[0025] S13: subjecting the stirred mixed solution to a hydrothermal reaction in a sealed autoclave;

[0026] S14: The reactant obtained in S13 is washed with water and anhydrous ethanol, and dried to obtain the bismuth / organic microspheres.

[0027] Preferably, the mass ratio of the bismuth nitrate pentahydrate, polyvinyl pyrrolidone, sodium bromide and glucose is 4-5:4:1-2:1-2; the magnetic stirring time of the six mixtures of bismuth nitrate pentahydrate, polyvinyl pyrrolidone, sodium bromide, glucose, ethylene glycol and 10% nitric acid solution is 10 minutes; the hydrothermal reaction is kept at 150°C to 160°C for 12h to 13h, and the specification of the autoclave is 100ml.

[0028] Preferably, the sintering method in S20 is: placing the bismuth / organic microspheres obtained in S10 in a tube furnace, and calcining them under the protection of an inert gas to obtain nitrogen-doped bismuth / carbon composite microsphere materials.

[0029] Preferably, the calcination method in S20 is: heating to 400°C to 450°C at a heating rate of 2°C / min to 5°C / min, and keeping the temperature for 1h to 2h; the inert gas is one of nitrogen or argon, or a mixture of the two.

[0030] The method uses bismuth salt as bismuth source, organic matter as carbon source and nitrogen source, the materials are simple and easy to obtain, and the cost is low. The target product is prepared by hydrothermal-carbonization method, the bismuth carbon structure is more compact, the material morphology is more uniform, and the problems of material deconstruction and poor uniformity caused by the unstable bismuth-carbon bonding interface in the traditional carbon coating method are avoided; the target product is prepared by hydrothermal-carbonization method, the method is simple, the preparation cycle is short, the output is considerable, and it is possible to produce on a large scale.

[0031] Thirdly, a nitrogen-doped bismuth / carbon composite microsphere material is proposed as a negative electrode material for sodium ion batteries.

[0032] The nitrogen-doped bismuth / carbon composite microsphere material prepared by the above technical solution and the method of the present invention has the following beneficial effects:

[0033] (1) The nitrogen-doped bismuth / carbon composite microsphere material provided by the present invention has low cost, the raw materials are all conventional materials, the preparation process is simple, the cycle is short, the yield is considerable, and there are no by-products;

[0034] (2) The nitrogen-doped bismuth / carbon composite microsphere material provided by the present invention has good crystallinity, stability, more active sites and moderate specific surface area;

[0035] (3) The nitrogen-doped bismuth / carbon composite microsphere material provided by the present invention has a single particle of micron-level size, and the nano-bismuth particles are evenly embedded in the material, which improves the space utilization rate and has a higher volumetric capacity. When used as a negative electrode material for sodium ion batteries, it can provide a higher sodium storage capacity within the limited space of the battery system, and has a very broad commercial application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The accompanying drawings illustrate exemplary embodiments of the present disclosure and together with the description serve to explain the principles of the present disclosure. These drawings are included to provide a further understanding of the present disclosure and are incorporated in and constitute a part of this specification.

[0037] Figure 1 These are scanning electron microscope images (SEM) and transmission electron microscope images (TEM) of the bismuth / organic matter microspheres in Example 1 of the present invention.

[0038] Figure 2 The present invention provides a scanning electron microscope (SEM) image and a transmission electron microscope (TEM) image of the nitrogen-doped bismuth / carbon composite microsphere material.

[0039] Figure 3 It is the X-ray diffraction pattern (XRD) of the nitrogen-doped bismuth / carbon composite microsphere material of the present invention.

[0040] Figure 4 This is an X-ray energy spectrum analysis (EDS) diagram of the nitrogen-doped bismuth / carbon composite microsphere material of the present invention, wherein the contents of carbon, nitrogen, oxygen and bismuth are 14.32wt%, 2.11wt%, 3.45wt% and 80.13wt% respectively.

[0041] Figure 5 This is a thermogravimetric analysis (TGA) diagram of the nitrogen-doped bismuth / carbon composite microsphere material of the present invention, wherein the content of metal bismuth is 85 wt %.

[0042] Figure 6 It is the XPS full spectrum and XPS-C1s, XPS-N1s, XPS-O1s, and XPS-Bi4f spectra of the nitrogen-doped bismuth / carbon composite microsphere material in the present invention.

[0043] Figure 7 The present invention shows the capacity-voltage curves of different cycle numbers at a current density of 5 A / g when the nitrogen-doped bismuth / carbon composite microsphere material is used as the negative electrode material of a sodium ion battery.

[0044] Figure 8 This is a cycle performance diagram of the nitrogen-doped bismuth / carbon composite microsphere material of the present invention as the negative electrode material of the sodium ion battery at a current density of 5A / g.

[0045] Fig. 9 This is a rate performance diagram when the nitrogen-doped bismuth / carbon composite microsphere material of the present invention is used as the negative electrode material of a sodium ion battery.

[0046] Fig.10 This is a cycle performance diagram of the nitrogen-doped bismuth / carbon composite microsphere material of the present invention as the negative electrode material of the sodium ion battery at a high current density of 20A / g. DETAILED DESCRIPTION

[0047] The nitrogen-doped bismuth / carbon composite microsphere material has a micron carbon sphere matrix material and a nitrogen-doped structure. The micron carbon sphere is evenly inlaid with a plurality of nano-bismuth particles, and each nano-bismuth particle is tightly wrapped by the carbon matrix to form a dense bismuth / carbon composite sphere. The nitrogen-doped structure can provide more active sites to provide higher capacity, and at the same time can effectively improve the conductivity of the carbon material matrix to make carrier transport faster. The carbon-wrapped bismuth particles have higher stability, and the presence of the carbon layer can inhibit the volume expansion of the bismuth particles during the charge and discharge process to a certain extent. The dense structure makes full use of the advantages of bismuth's high theoretical volume capacity, and can provide a higher sodium storage capacity in the limited space of the battery system, and has a very broad prospect for commercial application. The following is combined with Figures 1 to 10 The nitrogen-doped bismuth / carbon composite microsphere material and the preparation method thereof are described in detail.

[0048] The preparation method of the nitrogen-doped bismuth / carbon composite microsphere material of Example 1 of the present invention comprises the following steps:

[0049] S10: preparing bismuth / organic microspheres;

[0050] S20: The bismuth / organic microspheres in S10 are sintered and carbonized to obtain nitrogen-doped bismuth / carbon composite microsphere materials.

[0051] In the above steps, S10 includes:

[0052] S11: dissolving bismuth nitrate pentahydrate, polyvinyl pyrrolidone, sodium bromide, and glucose in ethylene glycol and 10% nitric acid solution to obtain a mixed solution;

[0053] S12: continuously stirring the mixed solution under magnetic stirring at room temperature;

[0054] S13: subjecting the stirred mixed solution to a hydrothermal reaction in a sealed autoclave;

[0055] S14: The reactant obtained in S13 is washed with water and anhydrous ethanol, and dried to obtain the bismuth / organic microspheres.

[0056] Preferably, the mass ratio of the bismuth nitrate pentahydrate, polyvinyl pyrrolidone, sodium bromide and glucose is 4-5:4:1-2:1-2; the magnetic stirring time of the six mixtures of bismuth nitrate pentahydrate, polyvinyl pyrrolidone, sodium bromide, glucose, ethylene glycol and 10% nitric acid solution is 10 minutes; the hydrothermal reaction is kept at 150°C to 160°C for 12h to 13h, and the specification of the autoclave is 100ml.

[0057] Figure 1 The bismuth / organic microspheres are prepared in step S10 of preparing the nitrogen-doped bismuth / carbon composite microsphere material in Example 1 of the present invention, and have an average particle size of 4.9 μm.

[0058] In the above steps, S20 includes:

[0059] Preferably, the sintering method in S20 is: placing the bismuth / organic microspheres obtained in S10 in a tube furnace, and calcining them under the protection of an inert gas to obtain nitrogen-doped bismuth / carbon composite microsphere materials.

[0060] Preferably, the calcination method in S20 is: heating to 400°C to 450°C at a heating rate of 2°C / min to 5°C / min, and keeping the temperature for 1h to 2h; the inert gas is one of nitrogen or argon, or a mixture of the two.

[0061] Figure 2 is a scanning image (SEM) and a transmission image (TEM) of the nitrogen-doped bismuth / carbon composite microsphere material of Example 1 of the present invention, Figure 2 A micron carbon sphere matrix material of a nitrogen-doped bismuth / carbon composite microsphere material is shown, wherein a plurality of nano-bismuth particles are uniformly embedded inside the micro-carbon sphere, the average diameter of the nano-bismuth particles is 10 nm, and each nano-bismuth particle is tightly wrapped by the carbon matrix to form a dense bismuth / carbon composite sphere, the average diameter of which is 6.5 μm.

[0062] Figure 3 This is the X-ray diffraction pattern (XRD) of the nitrogen-doped bismuth / carbon composite microsphere material of Example 1 of the present invention, wherein 22.5°, 27.2°, 38.0°, 39.6°, 44.6°, 46.0°, 48.7°, 56.0°, 59.3, 62.2°, 64.5°, 67.4°, and 70.8° correspond to the (003), (012), (104), (110), (015), (113), (202), (024), (107), (116), (122), (018), and (214) crystal planes of metallic bismuth, respectively, showing good crystallinity of the nano-bismuth particles.

[0063] Figure 4 is an X-ray energy spectrum analysis diagram (EDS) of the nitrogen-doped bismuth / carbon composite microsphere material of Example 1 of the present invention, Figure 4 It shows that the four elements C, N, O, and Bi are evenly distributed in the nitrogen-doped bismuth / carbon composite microsphere material, wherein the contents of carbon, nitrogen, and oxygen are 14.32wt%, 2.11wt%, and 3.45wt%, respectively, and the content of bismuth is 80.13wt%, which is consistent with Figure 5 The bismuth content of 85 wt % shown in the thermogravimetric analysis (TGA) is close to that of the other 15 wt %, and is also close to the sum of the contents of the three elements carbon, nitrogen and oxygen. Figure 4 and Figure 5 The element contents measured by different methods are Figure 4It is the data measured by transmission electron microscope. The test area of ​​the sample is small and the overall accuracy is relatively poor. It can be used as a reference value. Figure 5 Thermogravimetric analysis can only measure the bismuth content, which is relatively accurate, but cannot measure the content of other elements. Figure 5 The measured data shall prevail. The content of other elements is not as important as that of bismuth. Figure 4 is the reference value.

[0064] Figure 6 The XPS full spectrum and XPS-C1s, XPS-N1s, XPS-O1s, and XPS-Bi4f spectra of the nitrogen-doped bismuth / carbon composite microsphere material of Example 1 of the present invention are shown in FIG. Figure 6 The XPS full spectrum of nitrogen-doped bismuth / carbon composite microspheres and the fine spectra of four elements, C, N, O, and Bi, are shown. The fine spectra clearly show the bonding mode of each element and the type of nitrogen in the nitrogen-doped structure, namely graphitic nitrogen (graphitic-N), pyridinic nitrogen (pyridinic-N) and pyrrolic nitrogen (pyrrolic-N).

[0065] Figure 7 This is the capacity-voltage curve of different cycle numbers at a current density of 5A / g when the nitrogen-doped bismuth / carbon composite microsphere material of Example 1 of the present invention is used as the negative electrode material of the sodium ion battery. The first three cycles are battery cycle activation, and the current density is 0.1A / g. The discharge and charge specific capacity of the first cycle is 442 / 326mAh / g, and the corresponding initial coulomb efficiency (ICE) is 74%. The initial capacity loss can be attributed to the formation of the SEI layer and the side reaction between the carbon matrix and the electrolyte. The current density of the subsequent 4 to 4000 cycles is 5A / g. The good overlap of the charge and discharge curves reflects that the nitrogen-doped bismuth / carbon composite microsphere material has excellent reversibility in the process of sodium insertion and sodium removal.

[0066] Figure 8 This is a cycle performance diagram of the nitrogen-doped bismuth / carbon composite microsphere material of Example 1 of the present invention as the negative electrode material of the sodium ion battery at a current density of 5A / g. The first three cycles in the figure are 0.1A / g low current activation, and the current density is 5A / g from the fourth cycle. The discharge specific capacity of the fourth cycle is 294mAh / g. After 4000 cycles, the capacity is almost not decayed, showing its excellent cycle stability.

[0067] Fig. 9This is a rate performance diagram of the nitrogen-doped bismuth / carbon composite microsphere material of Example 1 of the present invention as the negative electrode material of a sodium ion battery. When the current density increases from 0.1A / g (the discharge capacity is 339mAh / g at this time) to 100A / g (the discharge capacity is 261mAh / g at this time), the capacity retention rate is 77%. Even at an ultra-high current density of 200A / g, the capacity is still 154mAh / g. At this time, it only takes 5.5 seconds to complete a charge and discharge process, and it can still recover to 1A / g and circulate stably. The material shows very good rate performance and has a very broad application prospect.

[0068] Fig.10 This is a cycle performance diagram of the nitrogen-doped bismuth / carbon composite microsphere material of Example 1 of the present invention as the negative electrode material of a sodium ion battery. After 2000 cycles at a high current density of 20 A / g, the capacity is still 303 mAh / g. Compared with the capacity of 326 mAh / g at the fourth cycle of the initial cycle, the capacity retention rate is 93%, and the cycle stability is excellent.

[0069] The following is a further description of the preparation method of the nitrogen-doped bismuth / carbon composite microsphere material of the present invention through specific implementation data:

[0070] Embodiment 1:

[0071] S10: 0.485 g of bismuth nitrate pentahydrate, 0.4 g of polyvinyl pyrrolidone, 0.1 g of sodium bromide and 0.1 g of glucose were added to a mixed solution of 50 ml of ethylene glycol and 10 ml of 10% nitric acid in sequence, and stirred at room temperature for 10 min. The mixed solution was then transferred to a 100 ml sealed Teflon-lined stainless steel autoclave and kept at 160°C for 13 h. After natural cooling, the mixture was centrifuged three times with water and ethanol respectively, and the collected samples were dried in an electric blast drying oven at 60°C overnight. After cooling, bismuth / organic microspheres were obtained.

[0072] S20: placing the bismuth / organic microsphere powder sample in a tubular furnace and calcining it under nitrogen (N2) protection, heating the temperature to 450°C at a heating rate of 2°C / min, keeping the temperature for 2h, and obtaining nitrogen-doped bismuth / carbon composite microsphere material after cooling.

[0073] The prepared nitrogen-doped bismuth / carbon composite microsphere material was used as the negative electrode material for sodium ion battery assembly and characterization: it was cycled 4000 and 2000 times at current densities of 5A / g and 20A / g, respectively, and the rate performance was tested at different current densities from 0.1A / g to 200A / g.

[0074] Example 2: The difference from Example 1 is that the mass ratio of bismuth nitrate pentahydrate, polyvinyl pyrrolidone, sodium bromide and glucose in S10 is 4:4:1:1, and the other steps are the same as those in Example 1, and a nitrogen-doped bismuth / carbon composite microsphere material is prepared, wherein the average diameter of the nitrogen-doped bismuth / carbon composite microsphere material is 3 μm, the average diameter of the bismuth nanoparticles is 5 nm, the mass fraction of bismuth is 76%, and the specific surface area is 90 m 2 / g.

[0075] Example 3: The difference from Example 1 is that the mass ratio of bismuth nitrate pentahydrate, polyvinyl pyrrolidone, sodium bromide and glucose in S10 is 5:4:1:1, and the other steps are the same as those in Example 1, and a nitrogen-doped bismuth / carbon composite microsphere material is prepared, wherein the average diameter of the nitrogen-doped bismuth / carbon composite microsphere material is 9 μm, the average diameter of the bismuth nanoparticles is 13 nm, the mass fraction of bismuth is 90%, and the specific surface area is 70 m 2 / g.

[0076] Example 4: The difference from Example 1 is that the mass ratio of bismuth nitrate pentahydrate, polyvinyl pyrrolidone, sodium bromide and glucose in S10 is 4:4:2:2, and the other steps are the same as those in Example 1, and a nitrogen-doped bismuth / carbon composite microsphere material is prepared, wherein the average diameter of the nitrogen-doped bismuth / carbon composite microsphere material is 6 μm, the average diameter of the bismuth nanoparticles is 8.6 nm, the mass fraction of bismuth is 87%, and the specific surface area is 74 m 2 / g.

[0077] Example 5: The difference from Example 1 is that the mass ratio of bismuth nitrate pentahydrate, polyvinyl pyrrolidone, sodium bromide and glucose in S10 is 4:4:1:2. The other steps are the same as those in Example 1, and a nitrogen-doped bismuth / carbon composite microsphere material is prepared, wherein the average diameter of the nitrogen-doped bismuth / carbon composite microsphere material is 5.2 μm, the average diameter of the bismuth nanoparticles is 7.8 nm, the mass fraction of bismuth is 79%, and the specific surface area is 85 m 2 / g.

[0078] Example 6: The difference from Example 1 is that the heating temperature in S10 is 150°C and the holding time is 12h. The other steps are the same as those in Example 1, and a nitrogen-doped bismuth / carbon composite microsphere material is prepared, wherein the average diameter of the nitrogen-doped bismuth / carbon composite microsphere material is 4μm, the average diameter of the bismuth nanoparticles is 6nm, the mass fraction of bismuth is 79%, and the specific surface area is 84m 2 / g.

[0079] Example 7: The difference from Example 1 is that the centrifugal collection in S10 uses water and ethanol twice each, and the other steps are the same as Example 1, to prepare nitrogen-doped bismuth / carbon composite microsphere material, wherein the average diameter of the nitrogen-doped bismuth / carbon composite microsphere material is 4 μm.

[0080] Example 8: The difference from Example 1 is that in S10, suction filtration is used for collection, and the other steps are the same as those in Example 1, to prepare a nitrogen-doped bismuth / carbon composite microsphere material, wherein the average diameter of the nitrogen-doped bismuth / carbon composite microsphere material is 8 μm.

[0081] Example 9: The difference from Example 1 is that the heating rate of the tube furnace in S20 is 5°C / min, and the other steps are the same as those in Example 1, and a nitrogen-doped bismuth / carbon composite microsphere material is prepared with a specific surface area of ​​88 m 2 / g.

[0082] Example 10: The difference from Example 1 is that the protective atmosphere used in the tube furnace in S20 is argon atmosphere (Ar), and the other steps are the same as in Example 1, and a nitrogen-doped bismuth / carbon composite microsphere material is prepared, wherein the average diameter of the nitrogen-doped bismuth / carbon composite microsphere material is 8 μm, the average diameter of the bismuth nanoparticles is 12 nm, the mass fraction of bismuth is 80%, and the specific surface area is 80 m 2 / g.

[0083] Although the present invention has been specifically shown and described in conjunction with the preferred embodiments, it should be understood by those skilled in the art that any equivalent substitutions or partial substitutions of the present invention in form and details, without departing from the spirit and scope of the present invention as defined in the appended claims, shall fall within the scope of protection of the present invention.

Claims

1. A nitrogen-doped bismuth / carbon composite microsphere material, characterized in that: The invention comprises a micron carbon ball matrix material, wherein a plurality of nano-bismuth particles are uniformly embedded inside the micro-carbon ball, and each nano-bismuth particle is tightly wrapped by the carbon matrix to form a dense bismuth / carbon composite ball, and a nitrogen-doped structure; the nano-bismuth particles are wrapped by a carbon layer, and a flaky carbon layer is formed on the surface of the bismuth / carbon composite ball; the mass fraction of the nano-bismuth particles in the bismuth / carbon composite ball is 79% to 90%; and the types of nitrogen in the nitrogen-doped structure are graphite nitrogen, pyridine nitrogen, and pyrrole nitrogen.

2. A nitrogen-doped bismuth / carbon composite microsphere material according to claim 1, characterized in that: The average diameter of the micron carbon spheres is 3 μm to 9 μm.

3. The nitrogen-doped bismuth / carbon composite microsphere material according to claim 1, characterized in that: The average diameter of the nano-bismuth particles is 5 nm to 13 nm.

4. The nitrogen-doped bismuth / carbon composite microsphere material according to claim 1, characterized in that: The specific surface area of ​​the nitrogen-doped bismuth / carbon composite microsphere material is 70 m 2 / g~90 m 2 / g.

5. A method for preparing nitrogen-doped bismuth / carbon composite microsphere material, characterized in that: The steps include: S10: Preparation of bismuth / organic microspheres; S20: The bismuth / organic microspheres in S10 are sintered and carbonized to obtain nitrogen-doped bismuth / carbon composite microsphere materials; The S10 includes: S11: dissolving bismuth nitrate pentahydrate, polyvinyl pyrrolidone, sodium bromide and glucose in ethylene glycol and 10% nitric acid solution to obtain a mixed solution; S12: continuously stirring the mixed solution under magnetic stirring at room temperature; S13: subjecting the stirred mixed solution to a hydrothermal reaction in a sealed autoclave; S14: washing the reactant obtained in S13 with water and anhydrous ethanol, and drying to obtain the bismuth / organic microspheres; The mass ratio of bismuth nitrate pentahydrate, polyvinyl pyrrolidone, sodium bromide and glucose is 4-5:4:1-2:1-2; the magnetic stirring time of the six mixtures of bismuth nitrate pentahydrate, polyvinyl pyrrolidone, sodium bromide, glucose, ethylene glycol and 10% nitric acid solution is 10 minutes; the hydrothermal reaction is kept at 150°C to 160°C for 12 hours to 13 hours; The sintering method in S20 is as follows: placing the bismuth / organic microspheres obtained in S10 in a tubular furnace, heating to 400°C to 450°C at a heating rate of 2°C / min to 5°C / min in a nitrogen or argon atmosphere or a mixed atmosphere of the two, and keeping the temperature for 1 h to 2 h, and obtaining nitrogen-doped bismuth / carbon composite microsphere material after natural cooling.

6. Use of the nitrogen-doped bismuth / carbon composite microsphere material prepared by the method for preparing the nitrogen-doped bismuth / carbon composite microsphere material according to any one of claims 1 to 4 or the nitrogen-doped bismuth / carbon composite microsphere material according to claim 5 as a negative electrode material for a sodium ion battery.